Moisture Changes in the Northern Xinjiang Basin Over the Past 2400 years as Documented in Pollen Records of Jili Lake - Xiao, Yulin; Xiang, Lixiong; Huang, Xiaozhong; Mills, Keely; Zhang, Jun; Chen, Xuemei; Li, Yuan (Frontiers in Earth Science, 2021)
Regional humidity is important for terrestrial ecosystem development, while it differs from region to region in inland Asia, knowledge of past moisture changes in the lower basin of northern Xinjiang remains largely unclear. Based on a pollen record from Jili Lake, the Artemisia/(Amaranthaceae + Ephedra) (Ar/(Am+E)) ratio, as an index of regional humidity, has recorded four relatively dry phases: (i) 400 BCE to 1 CE, (ii) the Roman Warm Period (RWP; c. 1-400 CE), (iii) the Medieval Warm Period (MWP; c. 850-1200 CE) and (iv) the Current Warm Period (CWP; since 1850 CE). In contrast, the Dark Age Cold Period (DACP; c. 400-850 CE) and the Little Ice Age (LIA; c. 1200-1850 CE) were relatively wet. Lower lake levels in a relatively humid climate background indicated by higher aquatic pollen (Typha and Sparganium) after c. 1700 CE are likely the result of intensified irrigation for agriculture in the catchment as documented in historical records. The pollen Ar/(Am+E) ratio also recorded a millennial-scale wetting trend from 1 CE to 1550 CE which is concomitant with a long-term cooling recorded in the Northern Hemisphere.